PENGARUH INDUSTRI PENGOLAHAN, PENYEDIAAN AKOMODASI DAN MAKAN MINUM, TRANSPORTASI DAN PERGUDANGAN TERHADAP PDRB DI KABUPATEN DELI SERDANG - Oktavia S, Putri; Hidayat, Toni (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2023)
This study aims to study how the manufacturing industry, food and beverage providers, transportation and storage have an impact on Deli Serdang's regional gross domestic product (GRDP). These findings are quantitative using secondary data obtained from the Deli Serdang Regency Central Statistics Agency in 2012–2021. In this research, the analysis method is multiple linear regression, and Eviews 12 is used. The test results show that variables in processing, lodging and food, transportation and warehousing have an important influence on the GRDP of Deli Serdang Regency. Simultaneously, variables in the processing industry, living and eating facilities, transportation, and warehousing have an influence related to GRDP in Deli Serdang Regency, with a Fcount value greater than Ftable (89.92216 greater than 4.76) with a prob value of 0.000022